2001
DOI: 10.1116/1.1349194
|View full text |Cite
|
Sign up to set email alerts
|

Nature of oxygen at rocksalt and spinel oxide surfaces

Abstract: The chemical environment of oxygen in cobalt-containing metal oxides with compositions͑M,MЈϭMn,Ni,Co͒ has been studied by Auger, x-ray and ultraviolet photoelectron, and high resolution electron energy loss spectroscopies. While there is a single type of lattice oxygen in the bulk structure of simple rocksalt and spinel oxides, the nature of oxygen at the surface of the spinel oxides is considerably more complex. Photoemission from core oxygen states in these materials often shows multiple peaks and satellite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…X-ray photoemission (XPS) from C 1s and O 1s spectral regions showed carbonate to be detectable by XPS for some, although not all, of the samples studied, as will be described in detail below. poses and have been obtained on well-defi ned single crystal substrates [45], [46] and [47]. The Co 2p spectra of the lithium-containing oxides are characteristic of Co 3+ in an octahedral or near-octahedral environment, as is also observed for the spinel Co 3 O 4 structure.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…X-ray photoemission (XPS) from C 1s and O 1s spectral regions showed carbonate to be detectable by XPS for some, although not all, of the samples studied, as will be described in detail below. poses and have been obtained on well-defi ned single crystal substrates [45], [46] and [47]. The Co 2p spectra of the lithium-containing oxides are characteristic of Co 3+ in an octahedral or near-octahedral environment, as is also observed for the spinel Co 3 O 4 structure.…”
Section: Resultsmentioning
confidence: 96%
“…At 529.2 eV, the value for the LiCoO 2 sample is equal to or only slightly lower than that reported for lattice oxygen in Co 3 O 4 (529.2-529.5 eV; refs. [53], [54], [55] and [56]), and slightly lower than that for CoO (529.4-529.6 eV; refs. [53], [55], [56], [57] and [58]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depth dependent measurements using higher photon energies (see also below) indicated that the peak at 530.3 eV is to a large extent due to sub-surface species. However the position of this peak is shifted about 0.8 eV as compared to that of the lattice oxygen peak of CoO and Co 3 O 4 oxides (at 529.5 ± 0.2 eV), reported in the literature [30] and measured on reference compounds in the same set-up [31]. The interpretation of 530.3 eV peak will be given below in combination with other results.…”
Section: Comparison Of Srm and Wgs Reactions Over Ptruco Catalystmentioning
confidence: 77%
“…Cobalt (Fig. 2c) is mainly in the oxide form under WGS reaction conditions, as indicated by the BE position of the main peak at 780.4 eV and the intense satellite structure at the high BE side [29] and [30]. Comparison with reference a CoO spectrum reveals an extra bump to the low BE side of the peak (indicated by an arrow).…”
Section: Comparison Of Srm and Wgs Reactions Over Ptruco Catalystmentioning
confidence: 99%